2004
DOI: 10.1177/13670069040080030601
|View full text |Cite
|
Sign up to set email alerts
|

First language attrition and syntactic subjects: A study of Greek and Italian near-native speakers of English

Abstract: In this paper we present some results from an experimental study that we have been conducting into the effects of syntactic attrition on the L1 of Greek and Italian speakers who have achieved near-native proficiency in their L2 (English) but still use their L1 on a regular basis. In particular, we test the hypothesis, developed on the basis of assumptions regarding syntactic modularity, that the changes in L1 syntax will be restricted to the interface with the conceptual / intentional cognitive systems. The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
427
5
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(495 citation statements)
references
References 19 publications
(12 reference statements)
35
427
5
11
Order By: Relevance
“…Therefore, following previous studies on L1 attrition, this long-term exposure to the L2 combined with limited exposure to the L1 is sufficient for syntactic attrition to occur (e.g. Tsimpli et al 2004). Moreover, their English near-nativeness was also assessed with the questionnaire and during the recruiting process and the experimental session.…”
Section: Participantsmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, following previous studies on L1 attrition, this long-term exposure to the L2 combined with limited exposure to the L1 is sufficient for syntactic attrition to occur (e.g. Tsimpli et al 2004). Moreover, their English near-nativeness was also assessed with the questionnaire and during the recruiting process and the experimental session.…”
Section: Participantsmentioning
confidence: 78%
“…bilingual children, near-native speakers and L1 attriters). Previous research addressed aspects such as the effects of The final publication is available at Springer via http://dx.doi.org/10.1007/s10936-015-9372-4 4 semantic or discourse factors in the acquisition of word order (Belletti et al 2007;Hertel 2003;Hopp 2009;Lozano 2006;Montrul 2004a;Wilson 2009), or the influence of pragmatics in the acquisition of null versus overt pronominal subjects and objects (Argyri and Sorace 2007;Belletti et al 2007;Lozano 2009;Montrul 2004b;Paradis and Navarro 2003;Rothman 2009;Serratrice et al 2011;Serratrice et al 2004;Tsimpli et al 2004). Structures that are sensitive to pragmatic or contextual conditions have been an especially privileged ground for research.…”
Section: Introductionmentioning
confidence: 99%
“…Initially suggested for the very advanced level of ultimate attainment in L2 acquisition, the IH has been expanded to bilingual first language acquisition (BFLA) and initial stages of L1 attrition. Several studies (Mueller & Hulk, 2001;Paradis & Navarro, 2003;Tsimpli, Sorace, Heycock & Filiaci, 2004;Belletti, Bennati & Sorace, 2007;Haznedar, 2007) provided evidence supporting the IH by demonstrating that at syntax-discourse interface, language behavior of bilingual children in BFLA, as well as of adult learners at very advanced levels of L2 attainment differs from that of native speakers, and that syntax-discourse interface structures are vulnerable at the very early stages of attrition.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant research in SLA has shown that, as regards formal grammatical properties and operations in the narrow syntax, near-native competence can be reached despite the fact that these are often underdetermined by input (Tsimpli et al, 2004;Lozano, 2006Lozano, , 2008Lozano, , 2016Sorace and Filiaci, 2006;Tsimpli and Sorace, 2006;Tsimpli and Dimitrakopoulou, 2007;Tsimpli and Mastropavlou, 2007;Sorace and Serratrice, 2009). 16 By contrast, syntactic focus movement involves operations not only in the narrow syntax but, crucially, at the syntax-discourse interface: in Greek syntactic focus movement involves an (interpretable)…”
mentioning
confidence: 99%